Repurposing rural technical vocational education and training in South Africa - Mancotywa, Yoliswa Lindelwa (2023)
In South Africa, Technical Vocational Education and Training (TVET)1 is supposed to be instrumental in achieving the country’s National Development Goals and play an important role in addressing the country’s skills shortages, unemployment, poverty, and inequality. The persistent high youth unemployment, especially among rural communities, puts into question extant TVET policies that strive to equip youth with employability skills within formal sector, as opposed to skills within the context in which they live. The South African TVET system is based on a flawed theoretical understanding that fails to consider the broader social purposes of higher education. The researcher argues for the need to “rethink” the purpose of TVETCs (Technical Vocational Education and Training Colleges) in South Africa, particularly rural colleges that are struggling to develop a successful TVET in which a significant share of a typical youth cohort enrols and get meaningful training. The research examines what TVET education is doing, and what could be done to produce graduates with skills for work, life and society. The researcher advances the notion that TVET education is important, but the education system needs to move beyond preparing students for employability alone, when it is known that jobs might not be readily available, and that the economy is not expanding, particularly in rural areas. The researcher argues that what students value or have reason to value, the skills valued by the industry and in the local context, ought to a larger extent influence the education and training in rural colleges. The TVET education ought to produce graduates with capabilities for work, (students with employability skills influenced by the rural economy and skills), life (human development skills), and society (self-employment skills above the subsistence level). This implies that VET education ought to be intentional, more focused, and thus that colleges must establish strong institutional linkages with (rural) industry. Ultimately, the researcher proposes a Rural Integrated Vocational Education Training Approach (RIVETA), that advances CA perspectives, and provides a more expansive view of the role of rural TVETs. A qualitative research approach was adopted, and semi-structured interviews were used to gather in-depth information from students and lecturers. The sample comprised 21 students in Phase 1, six lecturers in Phase 2, and 13 students in Phase 3. The findings reveal that the students valued the knowledge and skills acquired from the college and hoped that their qualification would help them to move up the social ladder. Notably, students did not only value employability skills, but also human development skills, including entrepreneurship skills, self-esteem and confidence, recognition and respect, affiliation, social responsibility and resilience. However, conversion factors including TVET funding, college teaching, the curriculum, absence of practical sessions during learning, failure by students to access internships and poor-quality schooling, disabled students to achieve these skills. The data further reveals that none of the graduates reported to have been formally employed, thereby questioning the quality and relevance of the skills attained. In addition, although students valued entrepreneurship skills, the College inadequately imparted these skills to students, and only two graduates reported to have become entrepreneurs. Lecturers affirmed student views regarding the lack of practical sessions and internships for students, and the gaps in the curriculum. They argued that this compromised students in acquiring skills and knowledge relevant to the current world of work in South Africa. Lecturers also believed that students were not adequately equipped with Information Technology (IT) skills, social skills, and entrepreneurial skills, and attributed this to gaps within the curriculum. Overall, the RIVETA developed in this study provides a broader view of the kind of knowledge and skills that rural TVETCs ought to equip students within South Africa. The approach explores the TVET system in a rural area beyond productivity, by integrating elements of the expansive CA. Further, the approach shows how rural TVET graduates ought to be equipped with entrepreneurship, innovation, leadership skills and knowledge that cross boundaries and that are valued by industry as well as local communities. The findings of this study will assist policy practitioners and relevant stakeholders in improving rural TVET in South Africa by moving beyond the dialogue of skills development for employment and focusing on human development and entrepreneurial skills. RIVETA is equally important to producing responsible global citizens, who are capable of not only contributing to the economy, but to critical social engagements and debates within the broader economic and human development project.